Content: Evolution & Development 5–6/2016. Issue 5 (10th November 2016) - Unknown
Abstract : Cover image: Photograph of a male, juvenile, and female blue‐banded goby (Lythrypnus dali), a highly social hermaphroditic fish. Gobies utilize a highly conserved androgen pathway to sexually differentiate the genitalia early in life. This pathway is recaptured during adult sex change to alter genital morphology